Studies on the influence of chemical disinfection, ultraviolet irradiation and pipe matrix on biofilm composition in drinking water distribution systems - Matias, Fernando M. G (University of Ottawa (Canada), 2007)
There has recently been a shift in water treatment practices in Canada to a source-to-tap approach on water quality. With this approach comes the understanding that our water distribution systems are covered in biofilms which could contain potentially hazardous opportunistic pathogens. Meanwhile, regulations on control of disinfection byproducts in drinking water have also induced the phase-out of chlorine and its replacement with either chlorine dioxide or monochloramine in conjunction with UV treatment. These changes are based solely on the reduction of known disinfection byproducts and have not considered the impact of changing the disinfection regime on the ecology of biofilms within the distribution system. The objective of this study was to determine what, if any, influence changes in water disinfection would have on the mix of bacterial species in the distribution system biofilms with particular reference to cast iron and polycarbonate as pipe substrata. Classical culture-based methods can reveal only a fraction of the bacterial content of biofilms because of our rudimentary understanding of the nutritional requirements of the organisms present and their inter-dependency. In contrast, newer techniques in molecular biology have become the norm for studying microbial ecology as they are not subject to the limitations of the culture methods, and thus can provide a much better profile of bacterial populations in biofilms. Although these methods have their own biases, PCR-DGGE was selected to monitor any changes in the profiles of the biofilms obtained under different disinfectant regimes and identify similarities and differences. Identification of the bacterial species would then be obtained by the sequencing of cloned bands, and matching them to the online databases, BLAST and RDP II. Clear differences were observed in the biofilms from the two pipe materials tested. Aquabacterium parvum, Escherichia coli, Dechloromonas sp., Methylobacillus flagellatus, Phyllobacterium sp., Rhodocyclus sp., and Sphingomonas sp., were only identified in biofilms from cast iron coupons, while Chitinophaga sp., was found in biofilms from only polycarbonate coupons. This confirms that the pipe material can influence the types of organisms growing on its surface. In general, the bacterial profiles were similar in the presence or absence of upstream UV treatment, except for the uncultivable Flavobacterium spp., which was detected only in the absence of UV treatment. This indicated that UV treatment has a relatively minor impact on altering the biofilm composition. While a direct comparison between the impacts of the chemical disinfectants was not possible due to the design of the experimental set-up, the data obtained showed that several aspects of the bacterial profiles remained similar irrespective of the dosage levels of chlorine, chlorine dioxide, and monochloramine used.
Keywords: Biology, Microbiology.